Social media disinformation in the pre-electoral period in Portugal - Cardoso, G. (2020)
Since the North American presidential election of 2016, the role of social media on the propagation of misleading news and its instrumentalization by partisan groups has raised concerns. In this article we analyse the contents of 47 Facebook pages and 39 Facebook groups prior to the Portuguese parliamentary election of 6th of October of 2019 to track disinformation. Groups and pages to monitor were selected through a process that combined the number of fans or members, the proportion of political content, and the number of posts per week. We concluded that disinformative content was prevalent in the pages and groups monitored, that several political actors had a relevant influence on the debate and that most disinformation stemmed from the spinning of both mainstream and non-mainstream news to serve a political purpose.